Integrating Use Cases and Organizational Modeling - Santander, Victor F. A.; Castro, Jaelson F. B. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2002: Anais do XVI Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2002.23949, 2002)
The object oriented development paradigm has attracted many supporters in the Software Engineering community. One of the most important advances was the Unified Language Modeling (UML), a standard for visual modeling. Use Case Diagrams have been used for capturing system functional requirements. However, the system development occurs in a context where organization processes are well established. Therefore, we need to capture organizational requirements to define how the system fulfils the organization’s goals, why it is necessary, what are the possible alternatives, what are the implications to the involved parts, etc. Unfortunately, UML is ill equipped for modeling organizational requirements. We need other techniques, such as i*, to represent these aspects. Nevertheless, organizational requirements must be related to functional requirements represented as Use Cases. In this paper we present some guidelines to assist requirement engineers in the development of Use Cases from the organizational models represented by the i* technique.